Market potential study of NutrioTM biofertilizer for sugarcane and eggplant - Manipol, Nohreen Ethel P.; Labilles, Ericka Shane R. (Annals of Tropical Research, 2023)
NutrioTM is a new foliar spray biofertilizer inoculant containing endophytic bacteria that has been tested for improved yield of sugarcane. The product has also been proven effective for eggplant production. Although NutrioTM has already been in the market, it was still operating on a small-scale during the time this research was conducted. This PCAARRD-funded study looked into the market potential of NutrioTM as biofertilizer for sugarcane and eggplant. Specifically, this research aimed to a) define the potential market for NutrioTM, which was anchored on the sugarcane and eggplant commodity systems analyses, b) determine the level of awareness, perceptions/evaluations and willingness of the potential market to use/buy NutrioTM, c) estimate the market requirements for NutrioTM, d) identify market-related challenges toward the commercialization of NutrioTM and e) recommend pathways for the commercialization of Nutrio.TM Three provinces were randomly selected for each commodity, namely, Batangas, Iloilo and Negros Occidental (for sugarcane), and Pangasinan, Iloilo and Cagayan (for eggplant). A total of 148 farmer-respondents were interviewed. Key informant interviews and literature review were also conducted. Both qualitative and quantitative data analyses were employed. NutrioTM biofertilizer can be considered as a promising technology based on the responses of the sugarcane and eggplant farmers interviewed. Among 148 respondents, 134 (91%) were willing to buy the product. Establishing a new enterprise for manufacturing and selling of the technology of 435,870.56 kilograms of the product for both sugarcane and eggplant market would be profitable. Furthermore, distribution of the product through existing enterprises would also be profitable, with an additional potential income of PHP64,523,630.00 if product distributorship would be adopted. Some strategies to expand the business scale of NutrioTM, such as the improvement of product packaging, product demonstration and field testing and product label expansion as well as adoption of distributorship for the technology to realize its full potential were recommended.